2017
DOI: 10.1080/00952990.2017.1318891
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ marijuana use, injuries, and emergency department visits

Abstract: Healthcare providers should screen for marijuana and other substance use among older adults and provide education about associated injury risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 23 publications
3
47
2
Order By: Relevance
“…Studies including relative measures showed frequency of ED utilization of three to 10 times that of comparison groups not using illicit drugs . Exceptions were a study in rural Taiwan, showing that people who inject heroin had a similar rate of ED presentation as the general population , and a study of older people who use cannabis in the United States showing similar odds of ED presentation as those who do not use cannabis .…”
Section: Resultsmentioning
confidence: 97%
“…Studies including relative measures showed frequency of ED utilization of three to 10 times that of comparison groups not using illicit drugs . Exceptions were a study in rural Taiwan, showing that people who inject heroin had a similar rate of ED presentation as the general population , and a study of older people who use cannabis in the United States showing similar odds of ED presentation as those who do not use cannabis .…”
Section: Resultsmentioning
confidence: 97%
“…Although better health was reported, older marijuana users have reported utilization of the emergency department ( Choi, Marti, DiNitto, & Choi, 2017 ; Schlaerth, Splawn, Ong, & Smith, 2004 ). In contrast to nonusers, marijuana use has been associated with injury among those in the older adult population, and injury has been associated with emergency department visits ( Choi, Marti, et al, 2017 ). Injury served as a mediator for the increased likelihood of emergency department utilization among marijuana users.…”
Section: Resultsmentioning
confidence: 99%
“…Marijuana use can negatively affect the health of those in the older adult population beyond abuse and dependence. Marijuana use has been associated with injury ( Asbridge et al, 2014 ; Blows et al, 2005 ; Choi, Marti, et al, 2017 ; Wettlaufer et al, 2017 ), mental health problems ( Choi et al, 2016 ; Choi et al, 2016a ; Hall & Degenhardt, 2009 ; Manrique-Garcia et al, 2012 ), cardiovascular disease ( Alshaarawy & Elbaz, 2016 ; Hackam, 2015 ; Hemachandra, McKetin, Cherbuin, & Anstey, 2016 ; Lindsay, Foale, Warren, & Henry, 2005 ; Reece, Norman, & Hulse, 2016 ), respiratory problems ( Howden & Naughton, 2011 ; Macleod et al, 2015 ; Martinasek, McGrogan, & Maysonet, 2016 ; Moore, Augustson, Moser, & Budney, 2005 ), metabolic syndrome ( B. A. Yankey, Rothenberg, Strasser, White, & Okosun, 2017 ; B. N. Yankey, Strasser, & Okosun, 2016 ), cancer ( Aldington et al,2008a , 2008b ; Zhang et al, 1999 ), unhealthy diet ( Foltin, Fischman, & Byrne, 1988 ; Smit & Crespo, 2001 ), and drug–drug interactions ( Lasota, 2015 ; Mahvan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These negative effects may also be increasingly common as OA are exposed to the exponential rising potency of THC and ratio of THC to CBD [53]. While OA marijuana use (particularly edibles) is associated with increased injury, emergency department visits, and driving under the influence [54][55][56], OA perceive less risk from using marijuana compared to their younger counterparts, particularly among frequent users, medical marijuana users, and in states where marijuana has been legalized [57]. Gerontology 2020;66:249-258 DOI: 10.1159/000504363…”
Section: Painmentioning
confidence: 99%